PORTRAYING HOW IMAGES ARE USED BY EFL TEACHERS IN THE TEACHING OF TEXTS - Samsam Maoladi; Vira Citra Mardiani; M. Jihad Abdul Matin; Pipih Setiawati; Setia Muljanto (IPI Garut Press, 2023)
Multimodal language literacy generates social and contextual ties and refers to the study of language combining two or more modes of meaning. This study aims to investigate how EFL teachers utilized pictures as a meaningful resource. Data collection was carried out face-to-face between teachers and students at one of Junior High Schools in Garut. In this study, an analysis was carried out to determine whether the teacher could explain an image in a text that produced meaning. The results of this analysis found that teachers only mastered limited multimodal competencies. This shows that teachers use pictures only to help teach texts, but teachers do not have enough teaching materials to use for teaching texts and only focus on textbooks when using pictures to make meaning. Then, based on these findings, it is suggested that teachers increase their competency in explaining multimodal meanings in texts so that images are used not only to create understandable learning materials but also to generate more meaning from texts. Based on these findings, it is recommended that teachers improve their ability to explain multimodal meanings in texts so that images are employed not just to make understandable learning materials, but also to generate additional meaning from texts.